The distance between us : a memoir - Grande, Reyna (Washington Square Press, 2022)
"Born in Mexico and raised by her grandparents after her parents left to find work in the U.S., at nine years old, Reyna enters the U.S. as an undocumented immigrant to live with her father. Filled with hope, she quickly realizes that life in America is far from perfect. Her father isn't the man she dreamed about all those years in Mexico. His big dreams for his children are what gets them across the border, but his alcoholism and rage undermine all his hard work and good intentions. Reyna finds solace from a violent home in books and writing, inspired by the Latina voices she reads. After an explosive altercation, Reyna breaks away, going on to become the first person in her family to obtain a higher education, earning a B.A. and then an M.F.A. in Creative Writing."